Multinomial Logistic Regression Analysis of Employee Performance in Certification Service Companies - Ahmad Tanzil Daulay; Fachrul Alam; Sawarni Hasibuan; Daruki Daruki; Mohamed Mansour (Journal of Applied Sciences and Advanced Technology, 2023)
This research was conducted at a service company engaged in the certification sector. The ability to handle a problem related to certification is the main requirement in determining the quality of services provided by the company. This study uses the Multinomial Logistic Regression Method which aims to find out the general description and the factors that affect employee performance in carrying out their daily work. This study uses primary data collected through online survey sheets for North Jakarta branch employees. The results of the study show that the factors that influence employee performance in certification service companies are the competence of the workforce in the form of Bachelor's degree educational background and work experience. For 6 years and employee training, while other factors have no significant effect.